Ketidakberwenangan Pengadilan dalam Menyelesaikan Sengketa Transaksi Kontrak Derivatif dalam Sistem Perdagangan Alternatif - Werleam, Hendrik; Kurnia, Ade (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the relative authority of the district court in examining derivative contract disputes in the Alternative Trading System (SPA), by examining Decision Number 357/Pdt.G/2020/PN Bdg jo. Number 655/PDT/2021/PT BDG. The main focus lies on the application of the principle of actor sequitur forum rei as regulated in Article 118 paragraph (1) HIR, which stipulates that civil lawsuits must be filed at the defendant's domicile. In this case, the defendant PT Valbury Asia Futures is domiciled in South Jakarta, while the lawsuit was filed with the Bandung District Court without any forum agreement or operational activities of the defendant in the area. The research method used is normative juridical, with a statutory approach and a case approach. The results of the study indicate that there is no valid reason to set aside the relative competence provisions. Therefore, the district court has no legal basis to examine the case and is obliged to declare the lawsuit inadmissible (niet ontvankelijk verklaard). This study also confirms that legal protection for consumers is important, but cannot be used as a basis for ignoring the formal provisions of imperative jurisdiction. The conclusion of this study is that the arbitration clause is unfair or made without adequate understanding from the consumer (customer), the court can test the validity of the clause by referring to Articles 4 and 18 of Law No. 8 of 1999 concerning Consumer Protection Law Number 8 of 1999. However, this must be proven first, not immediately becoming a basis for negating the validity of the arbitration clause. Keywords: Court Incompetence, Derivative Contracts, Alternative Trading Systems